Statistical Study of the Energetic Proton Environment at Titan's Orbit From the Cassini Spacecraft. Issue 6 (16th June 2018) - Regoli, L. H.; Roussos, E.; Dialynas, K.; Luhmann, J. G.; Sergis, N.; Jia, X.; Román, D.; Azari, A.; Krupp, N.; Jones, G. H.; Coates, A. J.; Rae, I. J.
Abstract: A statistical study of the energetic proton environment at Titan's orbit as captured by the MIMI/LEMMS and MIMI/CHEMS instruments is performed. The data analyzed cover all the dedicated flybys of Titan by Cassini as well as the orbit crossings that happen far from the moon. The energetic environment is found to be highly variable on timescales comparable to that of the duration of a flyby. Analysis of H + ion fluxes reveals a weak asymmetry in Saturn local time with the highest fluxes occurring in the premidnight sector of the magnetosphere. A correlation between the energetic ion fluxes and the location of Cassini in the magnetosphere with respect to the center of the current sheet can be observed. Finally, an empirical model of proton spectra for energies above 20 keV is derived based on fits to Kappa distribution functions. This model can be used to better understand the interaction of Titan with the magnetosphere and the energy deposition by energetic particles below the main ionospheric peak. Key Points: Energetic particle environment at Titan's orbit is highly variable Ion data present SLT asymmetry with higher fluxes in the premidnight sector Derivation of empirical model of ion spectra based on Kappa distribution function is presented